A new species of Proceroplatus Edwards (Diptera: Keroplatidae) in Miocene amber from the Dominican Republic - Penney, David; Evenhuis, Neal L.; Green, David I. (Zootaxa, 2013)
Keroplatid fungus gnats (Diptera: Keroplatidae) were hitherto known from the Caribbean island of Hispaniola from a single named species in Miocene amber from the Dominican Republic. Here we describe the new fossil species Proceroplatus preziosii Evenhuis & Penney based on a mature male specimen, which differs markedly from both fossil and extant taxa in the structure of its gonostyli and U-shaped wing pattern. We also document the first record of extant Keroplatidae, Proceroplatus pictipennis (Williston), from Hispaniola.